2019
DOI: 10.18662/rrem/146
|View full text |Cite
|
Sign up to set email alerts
|

Features of Authenticity Development in Future Psychologists

Abstract: The article addresses an acute problem of contemporary psychology-theoretical and empirical study of authenticity development of psychology students. The articles describes awareness of authenticity of psychologists as a professionally important integral personal characteristic based on a theoretical analysis of existing approaches in Ukrainian and foreign psychology. This construct implies respectful attention and fair treatment of oneself and own feelings, recognition of own value which makes clients feel th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Arnett (2007), proposed a new concept of "emerging maturity", which should more accurately characterize the period in which the university students are set and he situated it approximately within the range of 18 to 25 years. It was found that the emerging maturity in our conditions is characterized by a low level of stability and the search for own "self" (Codd, 2007;Radchuk et al, 2019). Lisa Lee (2007) examined, among other things, the relationship between perfectionism and age on a group of students (N = 301, of which 42 were men) with an average age of 18,26 years.…”
Section: The Typology Of Perfectionismmentioning
confidence: 99%
“…Arnett (2007), proposed a new concept of "emerging maturity", which should more accurately characterize the period in which the university students are set and he situated it approximately within the range of 18 to 25 years. It was found that the emerging maturity in our conditions is characterized by a low level of stability and the search for own "self" (Codd, 2007;Radchuk et al, 2019). Lisa Lee (2007) examined, among other things, the relationship between perfectionism and age on a group of students (N = 301, of which 42 were men) with an average age of 18,26 years.…”
Section: The Typology Of Perfectionismmentioning
confidence: 99%